PENGARUH PRODUCT QUALITY AND PRICE TERHADAP KEPUTUSAN PEMBELIAN ULANG SERAGAM SEKOLAH UD.JAYA ABADI - Junaidi Junaidi; Dedi Joko Hermawan; Muhammad Syarif Hidayatullah Elmas; Seger Priantono (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of product quality and price variables on the decision to repurchase UD.Jaya Abadi uniforms partially. The method in this study is quantitative, for a sample of 100 respondents who re-purchase UD. Jaya Abadi uniforms with the help of incidental sampling techniques. The method of collecting analytical data in this study comes from primary data based on the results of questionnaires. Then to process the data assisted with SPSS computer software. The results of the validity test and reliability test show that r count > r table, and from the total number of Cronbach Alpha values> 0.60 which indicates reliable. Based on the T test, the results of t count -0.511 < t table 1.985, and from the sig value obtained 0.611 > 0.05, it means that there is no influence of product quality on the decision to repurchase UD.Jaya Abadi uniforms and t count 23.821 > t table 1.985, and sig value 0.000 <0.05 it means that there is an influence of price on the decision to repurchase UD. Jaya Abadi uniforms.